Retrospective analysis of patiens with brain death - Eminoğlu, Şermin; Özgünay, Şeyda Efsun (The European Research Journal, 2019)
Objectives: We aimed to retrospectively analyze brain death cases in the our intensive care units. Methods: We examined archive records of brain death cases diagnosed between January 01, 2014 and October 01, 2018. We recorded patients’ demographics (age, gender, place of birth, blood type and diagnosis on admission), time to the preparation of the report, additional tests performed, rate of organ donation, donor rate, and number of organs removed. Results: A total of 151 brain death cases were detected. Of these, 69 were female. The average age was 53.96 ± 19.52years. A Rh + was the most common type (39.7%) in blood type analysis. Intracranial hemorrhage was the primary reason (54.3%) for admission. Apnea test was performed for 88 patients. Radiological imaging was used in 129 (85.4%) cases; computed tomography angiography being the most commonly performed method with 79 (52.3%) cases. Forty four patients’ families consented to organ donation. Considering the place of birth for donors, Marmara Region was the leader with 18 (40.9%) donors. Of the 82 brain death cases diagnosed with intracranial hemorrhage, 35 (42.68%) donated organs and this rate was significantly high (p = 0.002). The mean follow-up period for brain death was 1.49 days. Conclusions: Health team is responsible for identifying brain death and shoud be conscious about it, attempting to increase organ donation. They should act rapidly and avoid wasting time after the diagnosis. Family interviews to be conducted by an experienced and trained organ donation coordinator may increase donations by emphasizing the importance of organ donations. Giving wide media coverage to organ donation may increase awareness of the community of organ donation.﻿